ETosis: A Microbicidal Mechanism beyond Cell Death - Anderson B. Guimarães-Costa; Michelle T. C. Nascimento; Amanda B. Wardini; Lucia H. Pinto-da-Silva; Elvira M. Saraiva (Journal of Parasitology Research)
Netosis is a recently described type of neutrophil death occurring with the release to the extracellular milieu of a lattice composed of DNA associated with histones and granular and cytoplasmic proteins. These webs, initially named neutrophil extracellular traps (NETs), ensnare and kill microorganisms. Similarly, other cell types, such as eosinophils, mast cells, and macrophages, can also dye by this mechanism; thus, it was renamed as ETosis, meaning death with release of extracellular traps (ETs). Here, we review the mechanism of NETosis/etosis, emphasizing its role in diseases caused by protozoan parasites, fungi, and viruses.